2019
DOI: 10.22146/jh.44767
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusive Education for Deaf Children in Primary, Secondary and Preparatory Schools in Gondar, Ethiopia

Abstract: The purpose of this study was to investigate the current experiences of deaf children in upper primary, secondary and preparatory schools in Gondar City Administration, Ethiopia. A phenomenological study design with qualitative inquiry approach was used. The main tool used for the study was a semi-structured interview guide, which was developed out of comprehensive review of literature for data collection. Out of the thirty deaf children in the study (26 children from grades 5 to 8 and four children from grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Research, including studies by Foster S. et al, underscores the varied quality of social interactions experienced by deaf students in mainstream educational settings, ranging from fulfilling social lives to feelings of isolation (11). Furthermore, a study conducted in Ethiopia's Gondar City revealed that deaf students face significant barriers to academic and social inclusion, stemming from communication challenges, inconsistent teaching methodologies, and lowered teacher expectations regarding their capabilities (12). These findings accentuate the challenges of integrating hearing-impaired students into mainstream education, aligning with the broader objective of SDG4, which advocates for inclusive and equitable quality education for all, expanding beyond the scope of universal primary education to encompass outcomes in reading, numeracy, and broader learning domains (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Research, including studies by Foster S. et al, underscores the varied quality of social interactions experienced by deaf students in mainstream educational settings, ranging from fulfilling social lives to feelings of isolation (11). Furthermore, a study conducted in Ethiopia's Gondar City revealed that deaf students face significant barriers to academic and social inclusion, stemming from communication challenges, inconsistent teaching methodologies, and lowered teacher expectations regarding their capabilities (12). These findings accentuate the challenges of integrating hearing-impaired students into mainstream education, aligning with the broader objective of SDG4, which advocates for inclusive and equitable quality education for all, expanding beyond the scope of universal primary education to encompass outcomes in reading, numeracy, and broader learning domains (13,14).…”
Section: Introductionmentioning
confidence: 99%